Analysis of Urban Millennial's Financial Behavior: An Ethnography Study of Javanese and Minangnese on Managing Their Salary in Pursuing Wealth - Nur Ratna Komalasari; Mulyadi Mulyadi; Femil Ishak; Jerry Haikal (ARRUS Journal of Social Sciences and Humanities, 2024)
Personal financial management among urban millennials is influenced by several factors, such as cultural, financial literacy, and the courage to take risks. In this study, the author wants to recognize the pattern of salary management to achieve the welfare of urban millennials, mostly urban workers who come from various regions in Indonesia. The research focused on spending habits to save, understanding the types of investments, and their behavior and courage to invest, which is correlated to their ethnic cultural habits. This study employed a qualitative ethnographic technique by conducting direct interviews with 6 (six) respondents of the millennial generation aged 25-40 years from the Javanese and Minangkabau tribes. They are professional workers lived in the DKI Jakarta area and have a fixed income that comes from salary. Based on the results of the study, it reveals that the majority of respondents already have sufficient financial literacy and financial behavior by setting aside a portion of their income every month on a regular basis to be used as savings and invested. It can also be seen that their ethnic character influences the types of investments they choose.